An investigation of magnetic field distribution for assembly of magnets and its effect on alignment of steel fiber in aligned steel fiber-reinforced concrete - Xu, Mingfeng; Li, Hui; Mu, Ru (Frontiers in Materials, 2024)
The magnetic field method for preparing aligned steel fiber reinforced concrete (ASFRC) by solenoid coil has a limitation, which is that the specimen must be placed inside the solenoid coil, limiting its practical engineering application. To overcome this shortcoming, this study proposes a method for preparing ASFRCs using an external magnetic field created by assembled magnets. A theoretical model is proposed to predict the distribution of the external magnetic field and the orientation coefficient of ASFRCs prepared by assembled magnets. The predicted results are compared with the experimental results to verify the proposed model. Finally, flexural tests are used to compare the mechanical characteristics of ASFRCs prepared using assembled magnets and solenoid coil. The results indicate that the assembled magnets can be used to prepare the ASFRC with an orientation coefficient of 0.9 or higher, and the flexural strength is similar to that of the ASFRC prepared by the solenoid coil.